Medication Adherence and Antihypertensive Treatment Intensification on Blood Pressure Control at Bali Mandara Hospital - Desak Putu Meilinda Asri Swantari; Dita Maria Virginia; Phebe Hendra (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2026)
Controlling blood pressure (BP) in hypertension patients can reduce cardiovascular events. Efforts to improve BP control include enhancing medication adherence and intensifying antihypertensive treatment. This study aims to analyze the association of adherence and treatment intensification of antihypertensives with therapeutic outcomes among outpatients and assess the role of additional contributing factors. This retrospective cohort study at Bali Mandara Regional Hospital used patient medical records from April 2023 to March 2024. Subjects included outpatients on antihypertensive therapy, meeting inclusion and exclusion criteria. The independent variables were adherence, measured by Medication Possession Ratio (MPR), and treatment intensification, assessed based on the Treatment Intensification (TI) score. The dependent variable is a therapeutic outcome, BP, at the end of the study period. This study found a strong relationship between treatment intensification and improved BP control (p<0.05). However, there was no correlation between medication adherence and BP status. Patients with higher TI scores generally achieved better control over their BP. Individuals with TI scores < 0 had a 24 times higher chance of experiencing uncontrolled blood pressure compared to patients with higher TI scores. These findings highlight the critical role of treatment intensification in managing BP effectively.